Materiality analysis in sustainability and integrated reports. Issue 1 (6th January 2020) - Beske, Felix; Haustein, Ellen; Lorson, Peter C.
Abstract : Purpose: This paper aims to assess the disclosure on materiality analysis in sustainability and integrated reports through the lenses of legitimacy and stakeholder theory. The following three research questions are addressed: to what extent do companies report on their materiality analysis, what are the methods used for the analysis of the stakeholders and their topics/aspects and is there a higher disclosure of information of materiality assessment because of G4. Design/methodology/approach: The paper uses an archival research approach and deploys content analysis. Thus, a binary disclosure index was developed that indicates whether materiality related information are mentioned and explained in detail. The sample contains 132 reports from 33 companies of the German 110 HDAX stock market index between 2014 and 2017. Findings: The paper reveals that materiality analysis is a growing phenomenon. Nevertheless, companies disclose only a small amount of related information and fail to explain the methods for the stakeholder and topics/aspects identification. Thus, the underlying processes to define the report content remains unclear. Through the lenses of legitimacy theory, the study indicates that materiality analysis can strategically be misused to define report content without considering the interests of legitimized stakeholder groups and thus, does not improve the reports to those groups. Practical implications: Managers are urged to regard the importance of reporting about ongoing materiality assessments, as otherwise, concerns about the overall reliability of the information presented may arise. Social implications: Poor reporting about materiality assessments might lead to potential conflicts with stakeholders that do see their important topics not sufficiently reflected in the sustainability or integrated report. Originality/value: This study contributes to the literature regarding materiality in sustainability and integrated reporting and uses the assumptions of disclosure theories to evaluate the disclosure of a specific disclosure item.